Improving the fuel efficiency of an agricultural tractor diesel engine - Bolotokov Anzor; Gubzhokov Husen; Ashabokov Khachim; Troyanovskaya Irina; Voinash Sergey; Zagidullin Ramil; Sabitov Linar (E3S Web of Conferences, 2023)
The main reason for the emergence of the operational characteristics of tractor diesel engines is the uneven fuel consumption. Fuel equipment is one of the most responsible systems of diesel engines. The purpose of the study was to improve the fuel efficiency of an agricultural tractor diesel engine by using an injector sprayer. Modernization of the needle of the atomizer of the fuel injector is carried out by directing its guiding surface of the helical groove at an angle α, advancing the direction of the axisymmetric fuel pressure. This includes the fuel injector needle, as it is likely to be skewed, stuck, and dependent. The novelty of this design is protected by the patent of the Russian Federation RU 2231673. To assess the fuel efficiency, natural experiments of a diesel engine with serial and modernized injectors were carried out. The introduction of new technical equipment in the fuel equipment has led to the achievement of diesel engine power by 8 … 12% and the rate of retention of fuel consumption by 3 … 4%.